Vaginal surgery for the urologist - Nitti, Victor W.; Rosenblum, Nirit; Brucker, Benjamin M. (Female pelvic surgery video atlas series., 2012)
Part of the "Female Pelvic Surgery Video Atlas Series", this title enhances your skills in the diagnosis and management of pelvic disease. It provides discussions and illustrations, case studies, and video footage to clarify how to most effectively select and perform a variety of procedures and manage complications.